DIAGNOSTICS OF THE PATHOLOGY OF THE ENDOMETRIUM AND UTERINE CAVITY: HISTORY AND REAL PRACTICE - Юлия Сергеевна Фролова; Светлана Ивановна Елгина; Ольга Сергеевна Золоторевская (The Publishing House Medicine and Enlightenment, 2021)
The aim of the research - to conduct an analytical review of modern sources of scientific literature covering the issues of diagnostics of endometrial pathology. Materials and methods. The analysis of 36 domestic and foreign sources of literature on this topic. Results. Based on the results of the analysis of literature data, the understanding of the diagnosis of endometrial pathology at the present stage has been updated. Conclusion. Thus, the use of office hysteroscopy at the outpatient stage is an alternative for the diagnosis of endometrial pathology at the present time. The analysis shows that carrying out office hysteroscopy requires further widespread implementation in the practice of outpatient services.